Spondyloarthritis: State of the Art - Vinall, Maria (MD Conference Express, 2006)
Spondyloarthritis (SpA) are a group of diseases which includes ankylosing spondylitis (AS), reactive arthritis, arthritis/spondylitis with inflammatory bowel disease or psoriasis, and undifferentiated spondyloarthritis [Ann Intern Med 2002;136:896—907]. As a group, the SpA are one of the most common rheumatic diseases with a prevalence in the general population of 0.5—1.9% [Rheum Dis 2004;63:535—543]. This article discusses state-of-the-art treatments and therapies.